EFFECT OF CASH FLOW MANAGEMENT ON SHARE PRICE VOLATILITY OF OIL AND GAS FIRMS LISTED ON THE NIGERIAN EXCHANGE GROUP (Journal of Global Accounting, 2023)
The study determines the effect of cash flow management on the share price volatility of listed oil and gas firms in the Nigeria Exchange Group. The specific objective was to ascertain the effect of operating cashflow, financing cashflow, investing cashflow, and cash and cash equivalents on the share price volatility of the firms in focus. Ex-post facto research was adopted and panel data sourced from the annual reports of the sampled six (firms) from 2012 to 2021 were analysed using panel methodology approach. Hausman Specification Test and B-P Lagrange Multiplier Tests were preliminarily used to identify the best panel estimation tool for the study. Pooled Regression Analysis was adopted at 5% significance level which revealed that: operating cash flow, financing cash flow have a positive but non-significant effect on the share price volatility of listed oil and gas firms in Nigeria Exchange Group; investing cash flow has a significant positive effect on the share price volatility of the firms ; and  cash and cash equivalent has a negative and  non-significant effect on the share price volatility of listed oil and gas firms in Nigeria Exchange Group. It was concluded that when either of operating cashflow, investing cashflow or financing cashflow increases, share prices of listed oil and gas firms become more volatile. The study recommends that:  investors in the oil sector should validate the quality of earnings which oil and gas firms report by looking at their operating cash flows.it also recommended that  Oil and gas companies in Nigeria should secure more funding by capital raising or external borrowing in order to finance their expansion.it further recommended that  management of oil and gas firms seeking to appear good in their stock performance should invest more cash in profitable venture rather than overvaluing their accounting earning, finally,  management should ensure that excessive cash assets are not left idle since idle assets yield no return that will help make the firms’ stock performance appear good.
Keywords: Cash and Cash Equivalents; Cash Flow Management; Financing Cashflow; Investing Cashflow; Operating Cashflow; Share Price Volatility